2017
DOI: 10.1111/ajps.12290
|View full text |Cite
|
Sign up to set email alerts
|

Language Shapes People's Time Perspective and Support for Future‐Oriented Policies

Abstract: Can the way we speak affect the way we perceive time and think about politics? Languages vary by how much they require speakers to grammatically encode temporal differences. Futureless tongues (e.g., Estonian) do not oblige speakers to distinguish between the present and future tense, whereas futured tongues do (e.g., Russian). By grammatically conflating "today" and "tomorrow," we hypothesize that speakers of futureless tongues will view the future as temporally closer to the present, causing them to discount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 57 publications
(85 reference statements)
1
62
1
Order By: Relevance
“…Researchers investigating the effects of language on how people behave shows that, compared to speakers of languages with a strong present‐future distinction, speakers of languages with a weaker present‐future distinction smoke less, practice safer sex, have lower obesity rates, and save more for retirement—all behaviors that have traditionally been described as “future‐oriented,” yet are clearly beneficial for the individual's well‐being both now and in the future (Chen, ). Building on these correlational findings, a recent investigation showed that when bilingual respondents answered a survey in a weak future tense language (Estonian) vs. a strong future tense language (Russian), they discounted the future less and supported future‐oriented policies more (Pérez & Tavits, ).…”
Section: Reconstruing Timementioning
confidence: 99%
“…Researchers investigating the effects of language on how people behave shows that, compared to speakers of languages with a strong present‐future distinction, speakers of languages with a weaker present‐future distinction smoke less, practice safer sex, have lower obesity rates, and save more for retirement—all behaviors that have traditionally been described as “future‐oriented,” yet are clearly beneficial for the individual's well‐being both now and in the future (Chen, ). Building on these correlational findings, a recent investigation showed that when bilingual respondents answered a survey in a weak future tense language (Estonian) vs. a strong future tense language (Russian), they discounted the future less and supported future‐oriented policies more (Pérez & Tavits, ).…”
Section: Reconstruing Timementioning
confidence: 99%
“…Further, the LSH was confirmed by research concerning pro-environmental attitudes (Kim & Filimonau, 2017), environmental behavior and policies (Mavisakalyan et al, 2018) as well as future-oriented policies in general (Pérez & Tavits, 2017). Mavisakalyan et al, (2018), for example, followed Chen's (2003) setup, using panel data from the World Values Survey, finding speakers of weak FTR languages to be more willing to engage in costly pro-environmental actions, which was also evident across all countries (e.g., more climate change policies).…”
Section: From Economy To Health-psychology: the Explored And The Unexmentioning
confidence: 79%
“…They found significantly higher pro-environmental attitudes in Mandarin speakers suggesting a higher perceived urgency in proenvironmental topics when speaking a weak FTR language (i.e., the future was perceived as being closer). Pérez and Tavits (2017) randomly assigned Russian-Estonian bilinguals to either submit a survey about a "green tax" in Russian or Estonian (strong vs. weak FTR respectively) and found that answering the Estonian questionnaire led to more support for the "green tax", even after controlling for political conviction.…”
Section: From Economy To Health-psychology: the Explored And The Unexmentioning
confidence: 99%
“…Overstated results and hasty adoption may be hard to overturn. The study above linking language to economic behavior (Chen, 2013 ) was quickly taken onboard by economists and the data has been reused (Santacreu-Vasut et al, 2014 ; Hicks et al, 2015 ; Pérez and Tavits, 2017 ), even though the original findings are now in doubt (Roberts et al, 2015 , though see Mavisakalyan and Weber, 2017 ). The solution may mean that researchers need to spend more time refining the communication of their research, especially to non-specialist audiences.…”
Section: Discussionmentioning
confidence: 99%